Dynamic cervical plates in the cervical spine surgery (literature review) - Barysh, Oleksandr; Kozyryev, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
In cases of ventral stabilization of the cervical spine for anterior cervical interbody fusion (ACIF) they use rigid and dynamic cervical plates (СP). Recent experimental studies testify that dynamic CP are more effective comparing to rigid ones due to better load sharing between implants and interbody support which theoretically improves interbody fusion and minimizes the amount of complications associated with the implants. According to various authors amount of complications while using dynamic CP for ACIF is 2-22.6%. Purpose: to analyze results of the experimental studies and clinical application of the dynamic CP of different design according to scientific literature. Methods: for the systematization of materials on using of dynamic CP in the cervical spine surgery we analyzed specialized domestic and foreign literature. Predominantly we had to use predominantly English-language literature, because Russian-language articles contain data on using just rigid plates whereas information about dynamic CP is practically absent. Results: After analysis of scientific literature we explored history of development of dynamic CP, biomechanical features of ACIF with dynamic CP, concepts of subsidence of interbody support into the vertebral bodies, load sharing and stress shielding between interbody support and implants, results of experimental studies of the properties and clinical application of dynamic CP. Known classification of the cervical plates for ACIF was improved and expanded. Conclusions: Dynamic CP theoretically have got some advantages over previous generations of the cervical plates particularly in load sharing between interbody support, plate and screws confirmed by experimental studies. Application of dynamic CP allows achieving positive outcomes and better fusion signs comparing to rigid CP. However, there is likelihood that in cases of ACIF with dynamic CP in the process of subsidence some undesirable changes of segmental sagittal cervical contour and foraminal stenosis may occur. In some cases amount of pseudoartrosis and screw loosening may increase. Balance of dynamism and rigidity of fixation in abnormally changed cervical functional spinal units studied insufficiently and this requires further research.